Interruption of ghrelin signaling in the PVN increases high-fat diet intake and body weight in stressed and non-stressed C57BL6J male mice - Patterson, Zachary R.; Parno, Tamara J.; Isaacs, Albert M.; Abizaid, Alfonso (Frontiers in Neuroscience, 2013)
Chronic social stress has been associated with increased caloric intake and adiposity. These effects have been linked to stress induced changes in the secretion of ghrelin, a hormone that targets a number of brain regions to increase food intake and energy expenditure and promote increased body fat content. One of the brain sites targeted by ghrelin is the hypothalamic paraventricular nucleus (PVN), a region critical for both the regulation of the stress response and the regulation of energy balance. Given these data, we examined the contribution of ghrelin receptors in the PVN to the metabolic and behavioral changes that are seen during chronic social stress in mice. To do this, mice were implanted with cannulae attached to osmotic minipumps and delivering either vehicle or the ghrelin receptor (growth hormone secretagogue receptor) antagonist [D-Lys-3]-GHRP-6 (20 nmol/day/mouse). Following a week of recovery, half of the animals in each group were exposed to chronic social defeat stress for a period of 3 weeks whereas the other half were left undisturbed. During this time, all animals were given ad libitum access to standard laboratory chow and presented a high-fat diet for 4 h during the day. Results showed that the ghrelin receptor antagonism did not decrease stressed induced caloric intake, but paradoxically increased the intake of the high fat diet. This would suggest that ghrelin acts on the PVN to promote the intake of carbohydrate rich diets while decreasing fat intake and blockade of ghrelin receptors in the PVN leads to more consumption of foods that are high in fat.